Ranking of Regions of Russia by the Demographic Situation Considering the Level of Development of Social Infrastructure - R. V. Fattakhov; M. M. Nizamutdinov; V. V. Oreshnikov (Мир новой экономики)
The article discusses the formation of the demographic situation in Russia, considering the influence on them of the parameters of the development of social infrastructure. Today, most regions of the country are characterized by a decrease in population. Moreover, it is the level of development of medicine, education and other components of social infrastructure that determine the living conditions of the population and, as a result, the processes of natural and migration movement of the population. The study aims to determine the quantitative parameters of this relationship and the formation based on the results of the received rating of the administrative entities of the Russian Federation. In the framework of the work, we used methods of retrospective analysis, grouping, cluster analysis, correlation and regression analysis, and other methods. Further, we formed a list of indicators characterizing the level of development of the social infrastructure of the territory and highlighted groups of indicators. We proposed An approach to the formation of integral indicators of the level of development of social infrastructure for individual components of the population movement. The regions of the Russian Federation were grouped by the totality of the parameters of the demographic situation and socio-economic factors. As a result of testing the approach, we formed private and integral ratings of the regions of Russia according to the ratio of the parameters of the demographic situation and the level of development of social infrastructure. The results can be used in the development of the state demographic policy.